Analysis Of The Effect Of Dynamic Issues In Scheduling Of Flow Shop Environment - Ngatmi, Faharudin (Universiti Sains Malaysia, 2005)
This thesis is a study about the effect of dynamic issues in scheduling of flow shop environment. This flow shop scheduling was simulated with two dynamic issues based on two dispatching rules. Two dynamic characteristics selected are disturbance problem of machine breakdown and random arrival time for each job, meanwhile two dispatching rules selected are based on short processing time (SPT) and earliest due date (EDD). WITNESS simulation model was built to investigate the disturbance problems of dynamic issues in this flow shop scheduling. This model has six jobs and five machines were arranged in parallel line with concept of flow shop environment, in which the jobs was processed in a group of machines. The conclusion that we can get from the result analysis is comparison dynamic issues mostly influence the flow shop scheduling and which dispatching rule should be selected especially the rule that give short completion time and therefore giving good effect to the productivity of production system.